STRATEGI PENGELOLAAN RISIKO: MENGURANGI KERUGIAN PERUSAHAAN DARI PESANAN GAGAL BAYAR DAN STOCK YANG TIDAK SEIMBANG DENGAN PENDEKATAN KERANGKA COSO (STUDI KASUS : PT. SIGNAL NIAGA INDONESIA) - Dinda Putri Lestari; Sarah Yuliarini (Jurnal Ilmiah Akuntansi, 2025)
Increasingly fierce business competition demands companies to be able to manage risks strategically and in a structured manner. This study aims to analyze the risk management strategies implemented by PT. Signal Niaga Indonesia in dealing with defaulted orders and stock imbalances, using the COSO framework approach. The issues raised include excess stock due to unilateral cancellations by customers and the risk of default from the payment term system. The research method used is descriptive qualitative with a case study approach, through observation, interviews, and documentation. The results of the study indicate that the implementation of the five main components of the COSO framework-namely the control environment, risk assessment, control activities, information and communication, and monitoring-can help companies identify and control risks more effectively. Recommended strategies include evaluating customer creditworthiness, updating the stock recording system, and strengthening internal regulations. The implementation of these strategies has been proven to minimize financial losses and improve the company's operational efficiency. These findings are expected to serve as a reference for other distribution business actors in building a more adaptive and sustainable risk management system.